A new dynamic model for simultaneous saccharification and fermentation process of rice wine - Wang, Li; Zhang, Lihong; Guan, Tingting (Nonlinear Analysis: Modelling and Control, 2025)
In this paper, a new fractional model for the simultaneous saccharification and fermentation process of rice wine is proposed. To begin with, the existence and uniqueness of solution to the new model are proved by using some fixed point theorems. In addition, the stability at the equilibrium point and the Ulam–Hyers stability of the fractional simultaneous and saccharification fermentation model are analyzed. Then the approximate solutions of the fractional simultaneous saccharification and fermentation model are obtained by using the generalised Euler method. Finally, numerical simulations are given to verify the rationality of the fractional simultaneous saccharification and fermentation model. The new model proposed in this paper can more sensitively capture changes in the reaction.
Keywords: simultaneous saccharification and fermentation; fixed point theorem; stability analysis; generalized Euler method; numerical simulation